The Environmental Impact of Spine Surgery and the Path to Sustainability. Issue 8 (15th April 2023) - McNamee, Conor; Rakovac, Ana; Cawley, Derek T.
Abstract : Study Design: Narrative literature review. Objective: The aim of this study was to review published literature discussing sustainable health care and to identify aspects that pertain to spine surgery. Summary of Background Data: In recent years, research has investigated the contribution of surgical specialties to climate change. To our knowledge, no article has yet been published discussing the impact specific to spinal procedures and possible mitigation strategies. Methods: A literature search was performed for the present study on relevant terms across four electronic databases. References of included studies were also investigated. Results: Spine surgery has a growing environmental impact. Investigations of analogous specialties find that procurement is the single largest source of emissions. Carbon-conscious procurement strategies will be needed to mitigate this fully, but clinicians can best reduce their impact by adopting a minimalist approach when using surgical items. Reduced wastage of disposable goods and increased recycling are beneficial. Technology can aid remote access to clinicians, and also enable patient education. Conclusions: Spine-surgery–specific research is warranted to evaluate its carbon footprint. A broad range of measures is recommended from preventative medicine to preoperative, intraoperative, and postoperative spine care. Level of Evidence: 5.